IFN-γ production by brain-resident cells activates cerebral mRNA expression of a wide spectrum of molecules critical for both innate and T cell-mediated protective immunity to control reactivation of chronic infection with Toxoplasma gondii - Suzuki, Yasuhiro; Lutshumba, Jenny; Chen, Kuey Chu; Abdelaziz, Mohamed H.; Sa, Qila; Ochiai, Eri (Frontiers in Cellular and Infection Microbiology, 2023)
We previously demonstrated that brain-resident cells produce IFN-γ in response to reactivation of cerebral infection with Toxoplasma gondii. To obtain an overall landscape view of the effects of IFN-γ from brain-resident cells on the cerebral protective immunity, in the present study we employed NanoString nCounter assay and quantified mRNA levels for 734 genes in myeloid immunity in the brains of T and B cell-deficient, bone marrow chimeric mice with and without IFN-γ production by brain-resident cells in response to reactivation of cerebral T. gondii infection. Our study revealed that IFN-γ produced by brain-resident cells amplified mRNA expression for the molecules to activate the protective innate immunity including 1) chemokines for recruitment of microglia and macrophages (CCL8 and CXCL12) and 2) the molecules for activating those phagocytes (IL-18, TLRs, NOD1, and CD40) for killing tachyzoites. Importantly, IFN-γ produced by brain-resident cells also upregulated cerebral expression of molecules for facilitating the protective T cell immunity, which include the molecules for 1) recruiting effector T cells (CXCL9, CXCL10, and CXCL11), 2) antigen processing (PA28αβ, LMP2, and LMP7), transporting the processed peptides (TAP1 and TAP2), assembling the transported peptides to the MHC class I molecules (Tapasin), and the MHC class I (H2-K1 and H2-D1) and Ib molecules (H2-Q1, H-2Q2, and H2-M3) for presenting antigens to activate the recruited CD8+ T cells, 3) MHC class II molecules (H2-Aa, H2-Ab1, H2-Eb1, H2-Ea-ps, H2-DMa, H2-Ob, and CD74) to present antigens for CD4+ T cell activation, 4) co-stimulatory molecules (ICOSL) for T cell activation, and 5) cytokines (IL-12, IL-15, and IL-18) facilitating IFN-γ production by NK and T cells. Notably, the present study also revealed that IFN-γ production by brain-resident cells also upregulates cerebral expressions of mRNA for the downregulatory molecules (IL-10, STAT3, SOCS1, CD274 [PD-L1], IL-27, and CD36), which can prevent overly stimulated IFN-γ-mediated pro-inflammatory responses and tissue damages. Thus, the present study uncovered the previously unrecognized the capability of IFN-γ production by brain-resident cells to upregulate expressions of a wide spectrum of molecules for coordinating both innate and T cell-mediated protective immunity with a fine-tuning regulation system to effectively control cerebral infection with T. gondii.